Interfacial Applications in Environmental Engineering - Keane, Mark A (CRC Press, 2009)
Describing novel methods and catalytic strategies to conserve and maintain air, water, and soil quality, researchers from a range of disciplines discuss the role of interface science in environmental remediation. They detail approaches to separate, reuse, recover, and treat potentially valuable materials using techniques in ion exchange and adsorption; develop and design new catalysts to enhance production, energy, and cost efficiency; and evaluate and improve existing treatment strategies for recycling of plastics and wastes. The 17 studies were developed from presentations at the symposium Application of Interface Science to Environmental Pollution Control (Chicago, August 2001).